Application of the stereotype content model in marketing: a three-level review and future research. Issue 2 (4th October 2022) - Guo, Xiaoling; Liu, Hao; Zhang, Yicong
Abstract : Purpose: The aim of this research is to examine the application of the stereotype content model (SCM) in the field of marketing from macro (the country of origin), meso- (corporate image) and micro (service providers, brands, advertising and promotions) levels. Design/methodology/approach: This paper collects, reviews and summarizes the relevant literature, and prospects future research directions from three levels on this research topic. Findings: First, the authors contend that competence primacy popularizes in the early work but warmth becomes more influential recently. Second, they identify and discuss two doubts of the SCM in marketing, namely the moral dimension and the link between brands as intentional agents framework (BIAF) and the brand personality theory. Finally, they suggest several research avenues for the use of SCM in marketing research, including research on nation branding, emerging global brands and Confucianist cultures at macro level, artificial intelligence and warmth-as-competence strategy at meso-level, and brand personality and the brand animal logo at micro level. Originality/value: As an established framework in social psychology, the SCM has been increasingly applied in marketing research and a literature review in this light appears timely. This paper conducts for the first time a comprehensive review of the SCM in the marketing field on three levels, projects promising research directions, and thus contributes to the academia of marketing.